Epilithic diatoms of settlement of sivrice district (Hazar lake/Elazig-Turkey) - Pala, G.; Caglar, M.; Selamoglu, Z. (Green Wave Publishing of Canada, 2018)
In this study, the epilithic diatoms in the samples taken from two stations in Hazar Lake (Elazig-Turkey) between June 2015 and November 2015 were analyzed. In total, 28 taxa belonging to the diatoms were recorded during the study. The diatom taxa Cymbella (6 taxa), Navicula (4 taxa) and Nitzschia (4 taxa) were represented by the most taxa. © 2018, Green Wave Publishing of Canada. All rights reserved.
Keywords: Diatom; Elazig-Turkey; Epilithic; Sivrice district